Isolating a Culture of Son Preference Among Armenian, Georgian, and Azeri Parents in Soviet-Era Russia - Matthias Schief; Sonja Vogt; Elena Churilova; Charles Efferson (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper analyzes historical census data from the final Soviet census in 1989. We find that, even in the absence of sex-selective abortions, the fertility decisions of Armenian, Georgian, and Azeri parents living in Russia in the late 1970s and the 1980s were significantly more son-biased than those of other ethnic groups in Russia. This finding suggests that the observed increase in the sex ratio at birth in the Caucasus since the end of the Soviet Union at least partially reflects a deep-rooted cultural preference for sons. Moreover, this result supports one of the key hypotheses of gene-culture coevolution, namely the claim that cultural evolutionary processes can shape selection on the basic components of genetic fitness.
Keywords: J13; J16; Z10; 330; son preference; sex ratio; sex-selective abortions; historical census data; Caucasus; gene-culture coevolution